Prevalence and awareness of lower urinary tract symptoms among males in the Outpatient Clinics of Universiti Kebangsaan Malaysia Medical Centre. - Christopher Ho, CK; Praveen, S; Goh, EH; Tan, GH; Badrulhisham, B; Zulkifli, MZ; Khoo, HW; Su, XV; Ng, JY; Chong, LL; Lim, DW; Chen, ES; et al. (Penerbit UKM, 2011)
This study aims to determine the prevalence of lower urinary tract symptoms (LUTS) and level of awareness among male outpatients in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). A questionnaire consisting of demographic data, questions related to knowledge, attitude and practice on BPH and the International Prostate Symptom Score (IPSS) was used for this study. Uroflowmetry and bladder scan were used to evaluate the function of the urinary tract and severity of BPH. Urine dipstick was done for glycosuria, proteinuria and haematuria. A total of 220 respondents were surveyed. The prevalence of moderately and severely symptomatic LUTS was 42.7%. The most commonly reported LUTS were nocturia (78.2%), frequency (58.2%) and incomplete emptying (44.6%). The prevalence of glycosuria, proteinuria and haematuria were 23.6%, 11.4% and 1.8% respectively. There was a significant association between increasing age with the severity of LUTS (p=0.005). Out of 102 respondents with voided urine volume greater than 150 mL, there was a significant decrease in maximum (Qmax) (p=0.039) and average (Qave) urine flow rates with every 10 years increase of age (p=0.001). The majority of respondents (59.5%) have heard of BPH before. Over 78.2% of the respondents would seek medical attention if they have LUTS with 15.9% saying they would seek traditional treatment. In conclusion, the prevalence of LUTS was high and the level of awareness was satisfactory.